Wpływ wybranych struktur zależności na rozkład zagregowanych szkód - Wanat, Stanisław (On the Impact of Selected Dependence Structures on Aggregate Losses Distribution, 2008)
This paper discusses an approach to modeling of insurer's aggregate losses to incorporate the presence of dependencies. The paper begins by describing two dependence modeling techniques: common shock model and thinning-dependence structure. Next, using numerical illustrations, the sensitivities of the capital requirement and diversification benefit to the choice of the dependency modeling assumptions are investigated. The key conclusion is that there is a large variation in the capital requirement as well as diversification benefit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 450-457